Solar power to transform food systems and rural livelihoods: Evidence from a solar-powered cold storage intervention in Nigeria - Yamauchi, Futoshi; Takeshima, Hiroyuki (Springer, 2023)
In developing countries, a substantial amount of perishable and often highly nutritious commodities, such as fruits and vegetables, are lost after harvest, mainly caused by the lack of key infrastructures, such as electricity and cold chain facilities. On the other hand, the world has recently seen the potential of solar power in decarbonizing economies and transforming rural livelihoods in developing countries. A new technology, such as solar power photovoltaics, is highly divisible and, therefore, can be easily introduced to overcome the lack of sustainable electricity supply. In 2020–2021, we implemented an intervention to rebuild rural livelihoods in conflict-affected northeast Nigeria by building solar-powered cold storage facilities that can reduce food loss and increase consumption of perishable, micronutrient-rich horticulture products; increase incomes of market agents and producers; and improve employment. The intervention brought a significant increase in the number of days that horticulture products remain fresh, market sales for cold storage users, and the amount of vegetables available to the local population. Cost-benefit analysis showed a significant net economic gain in the long-run. Our example shows that a technological innovation, which overcomes the lack of an essential investment for development, can trigger economic transformation.